Calcium Aluminate based Cement as Dental Restorative Materials - Kraft, Lars (Uppsala universitet, Institutionen för materialvetenskap, 2002)
This thesis presents the results from the development process of a ceramic dental filling material based on calcium aluminate cement. The main focus of the work concerns dimensional changes during setting, hardening and curing and the understanding of the factors controlling the dimensional stability of the system. A range of compositions for research purposes and the composition of Doxadent™ – a dental product launched on the Swedish market in October 2000 – were evaluated. Furthermore hardness characteristics, flexural strength, porosity and microstructure studies are presented. The studies of dimensional changes led to a thorough investigation of the measuring devices used and their relevance. A split pin expander technique, very simple in function, has been evaluated and improved. The technique is considered to be adequate for detecting dimensional stability in restrained samples, thus mimicking the case for real fillings in most tooth cavities. The dimensional changes in the calcium-aluminate based cement system are mainly controlled by the grain size, the exact composition and the compaction degree. The expansion of the calcium-aluminate cement system was in the early work decreased from several percent down to only tenths of a percent. Results show that Doxadent™ has less than 0.2% in linear expansion after 200 days of storage in water. However, long-term tests have been unable to verify whether expansion stops with time. Long-term in-vitro studies of dimensional changes also affect the test equipment used, which is why the long-term behavior of the dimensional stability has to be clinically evaluated. The material integrates excellently with the tooth structure, has hardness and thermal properties similar to those of enamel and dentine, and is also biocompatible during hardening. A patented process for the preparation of wet compacted specimens was also developed.